"Blue-Slipped Stone-Burst" – Seeing Destructive Plasticity in Takuro Kuwata. (2nd January 2021) - Stent, David
Abstract: This article takes as its starting point speculative points of connection between the ceramic work of Takuro Kuwata and Aneta Regel, and selected writings by French philosopher Catherine Malabou on the notion of "destructive plasticity." Staging an experimental and unpredictable combination of sources, the text incorporates a variety of images concerning chance and repetition, form and matter, fluidity and fixity. It echoes Kuwata's method of hybridizing and exaggerating traditional and experimental techniques – for example, colliding the oversaturated image of contemporary Japan with the austere structures of the tea ceremony – in order to explore contingent relationships between them.